Embracing the Context of Pediatric Rehabilitation Programs: Investigating the Role of Family-centred Service Philosophy in Program Evaluation - Moreau, Katherine (Université d'Ottawa / University of Ottawa, 2012)
Program evaluation is becoming increasingly important in pediatric rehabilitation settings that adhere to FCS philosophy. This philosophy recognizes that each family is unique, that parents know their children best, and that optimal child functioning occurs within a family context. However, researchers know little about the specific evaluation activities occurring in these settings or the extent to which evaluators uphold FCS philosophy in their activities. The primary goal of this study is to examine the strengths, limitations, and consequences of current evaluation practice, including its compatibility with FCS philosophy. As a secondary goal, the study aims to understand the promise and prospects of alternative evaluation approaches that, in theory, are compatible with FCS philosophy. To address these goals, this study uses a mixed-methods approach and includes three phases. Phase 1 involves a survey of staff members involved with program evaluation at 15 Canadian pediatric rehabilitation centres. It determines the level of program evaluation occurring in these settings, verifies on the motivation for evaluation, and describes the degree to which evaluation activities are consistent with the FCS philosophy. Phase 2 involves interviews with staff members and explores the values, factors, and conditions that support and inhibit the evaluation of family-centred programs in pediatric rehabilitation settings as well as the benefits and limitations of using mainstream practices for evaluating these programs. Phase 3 then uses focus groups with staff members and interviews with parents to explore how the evaluation of family-centred programs can be improved as well as to identify the compatibility and practicality of using alternative evaluation approaches within these settings. Overall, the findings show that the amount of evaluation activities occurring within these centres is variable; that the majority of individuals working in program evaluation do not have formal training in it; and that the centres have limited resources for evaluation. The findings also demonstrate that participatory evaluation approaches are more compatible with FCS philosophy but that it might be difficult to implement such approaches given the limited resources and diverse characteristics of rehabilitation settings. In light of these circumstances, the study notes ways for improving program evaluation activities.
Keywords: program evaluation; participatory program evaluation; family-centred service; Canadian rehabilitation centres